Trade effects of transportation infrastructure among CAREC countries - Suprabha Baniya; Kiyoshi Taniguchi (Asian Development Bank (ADB), 2022)
This paper investigates the trade effects of transportation infrastructure reforms funded by the Asian Development Bank (ADB) in the Central Asia Regional Economic Cooperation (CAREC) program. To do this, we applied a combination of geographic information systems (GIS), econometric, and computable general equilibrium (CGE) analyses. Using GIS analysis, we compute the reduction in bilateral transport time and potential substitution across transportation modes induced by ADB-funded transportation reforms in the CAREC program. Then, using econometric analyses, we examine the direct impacts of transport time on the extensive and intensive margins of trade. We use the average geographical features of trade partners as the instruments of bilateral transport time to address the endogeneity between trade and infrastructure. Finally, implementing the partial equilibrium impacts of transport time reductions on trade in a firm-heterogeneity CGE model in the Global Trade Analysis Project (GTAP), we investigate the additional endogenous effects of transport time on trade. Combining the estimates of bilateral transport time reductions from the GIS analysis and the estimates of extensive and intensive margins of the trade from the two-part model, we find that the ADB transportation reforms in CAREC countries increase the trade values for existing exporters by 3.31% and trade participation by 1.21% on average. Using the CGE analysis, we find that trade values for CAREC countries increase by 2.04% to 8.72%, on average, due to additional endogenous effects on trade. We also find a positive change in total welfare for CAREC countries.
Keywords: R13; R41; F15; 330; CAREC; transportation infrastructure; trade pattern and time sensitivity; CGE analysis; GIS analysis